New variants in NLRP3 inflammasome genes increase risk for asthma and Blomia tropicalis-induced allergy in a Brazilian population - Queiroz, Gerson de A. (2020)
Coordenação de Aperfeiçoamento de Pessoal de Nível Superior -Brasil (CAPES) - Finance Code 001, National Research Council, Brazil (CNPq) and Foundation for Research Support of the State of Bahia (FAPESB). This study was also funded by Wellcome Trust, United Kingdom (Grant no. 072405/Z/03/Z).